(untitled) - Kramer, Glen (New York, 2005)
Ethernet Passive Optical Networks is the IEEE's (Institute of Electrical and Electronics Engineers) approved architecture of choice for the next generation of broadband access. Written by an author of the IEEE 802.3ah standard, this is the first book to explain the EPON architecture, analyze its performance, and annotate the standard. For any engineer or graduate student building equipment for broadband access or service provider offering such service, this will serve as the "authorized" guide to EPON.
Keywords: Ethernet (Local area network system),Passive optical networks.,Mạng nội bộ (hệ thống mạng nội bộ)